Carbene insertion into N–H bonds with size-selectivity induced by a microporous ruthenium–porphyrin metal–organic framework. Issue 11 (20th February 2018) - Chen, Lianfen; Cui, Hao; Wang, Yanhu; Liang, Xiang; Zhang, Li; Su, Cheng-Yong
Abstract : A stable and porous porphyrinic metal–organic framework Ru-PMOF-1 (Hf) has been prepared and used for N–H insertion reactions with high efficiency and selectivity. Abstract : A stable and porous porphyrinic metal–organic framework, Ru-PMOF-1 (Hf), has been prepared through the self-assembly of [5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrinato](monocarbonyl)ruthenium (Ru(TCPP)(CO)) and HfCl4 . Single-crystal X-ray diffraction analysis reveals that Ru-PMOF-1 (Hf) possesses a three-dimensional (3D) structure with orthogonal 1D open channels of 1.9 × 1.9 nm 2 . The porous nature has been confirmed by gas adsorption measurements. Its catalytic activity for the carbene insertion into N–H bonds has been investigated. The catalytic results indicate that Ru-PMOF-1 (Hf) is efficient for the insertion reactions of ethyl 2-diazoacetate (EDA) into a range of secondary amines with up to 92% yield, 938 TON and 2475 h −1 TOF. As an excellent heterogeneous catalyst, Ru-PMOF-1 (Hf) can be recovered and reused for at least ten runs with negligible loss of catalytic activity. Due to its uniform microporosity in three orthogonal directions, Ru-PMOF-1 (Hf), of which the particle sizes were carefully controlled by sieving, can induce size selectivity regarding the amine substrates. The reactivities of different unbranched dialkylamines, such as diethylamine (NHEt2 ), dibutylamine (NHBu2 ) and dipentylamine (NHPent2 ), have been compared, and the results display an apparent decreasing trend along the chain lengthening. For comparison, the corresponding nonporous and homogeneous catalyst Ru(TMCPP)(CO) (TMCPP = tetrakis(4-methoxycarbonylphenyl)porphyrin) displays negligible difference towards the reactions with these three amines.